Kompleksitas Fenomena Bullying pada Remaja dan Peran Strategis Bimbingan dan Konseling dalam Penanganannya - Denisa Septiani; Novi Fayza Widi Putantri; Risma Anita Puriani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study explores the complexity of bullying among adolescents and highlights the strategic role of guidance and counseling in addressing this issue. Using a literature review method, this research analyzes 20 scholarly articles published within the last ten years. The findings reveal that bullying behavior is influenced by a combination of internal and external factors, including peer conformity, excessive use of social media, ineffective parenting styles, and unsupportive school environments. Bullying manifests in various forms, such as verbal, physical, relational, and cyberbullying, with verbal bullying identified as the most prevalent. The impacts of bullying are significant and multifaceted, ranging from psychological distress, anxiety, trauma, and low self-esteem to decreased academic performance and social withdrawal. In some cases, victims may also develop aggressive tendencies and become perpetrators. Therefore, guidance and counseling services play a crucial role in mitigating bullying through comprehensive approaches, including preventive, curative, and developmental interventions. These efforts can be implemented through classroom guidance, individual and group counseling, and strong collaboration among counselors, teachers, parents, and the wider community. Creating a safe, supportive, and inclusive school environment is essential to effectively reduce bullying and promote adolescents’ well-being.